2020
DOI: 10.1016/j.injury.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infections with the Sinus Tarsi Approach in displaced intra-articular calcaneal fractures; a prospective cohort study with a minimum of one year follow-up

Abstract: Background: In the last decade, the sinus tarsi approach (STA) has gained interest over the extensile lateral approach (ELA) in the operative treatment of displaced intra-articular calcaneal fractures (DIACF's), mainly because of the lower rate of surgical site infections (SSIs). However, most studies are small and retrospective. The aim of this study was to evaluate the rate of SSIs of the STA in a large, prospective series of patients and to identify predictors for SSIs. Methods: In this prospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In the present study, we used a thoroughly selected population with a huge amount of sample to address the risk factors of DSSI following calcaneal fracture. It is of note, four out of five factors identified had been repeatedly investigated and their role was well‐established across studies with different levels of evidence 4,8‐10,19 . The only difference among them might be the determination of cut‐off values of BMI, for which we used both the traditional value (28.0 g/m 2 , for definition of obesity for Chinese people) and the current value of 26.4 kg/m 2 to make a dichotomization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we used a thoroughly selected population with a huge amount of sample to address the risk factors of DSSI following calcaneal fracture. It is of note, four out of five factors identified had been repeatedly investigated and their role was well‐established across studies with different levels of evidence 4,8‐10,19 . The only difference among them might be the determination of cut‐off values of BMI, for which we used both the traditional value (28.0 g/m 2 , for definition of obesity for Chinese people) and the current value of 26.4 kg/m 2 to make a dichotomization.…”
Section: Discussionmentioning
confidence: 99%
“…For some variables (smoking) volume and frequency might be particularly important parameters in infection complications, but detailed data were not available. Second, the volume of surgeon might affect the results, because surgical treatment of calcaneal fracture needs a learning curve, especially for tarsal sinus 19 . As plenty of surgeons perform operations, the sample size of operations for each surgeon in 1 year is too small to obtain effective statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that early ORIF within 1 week carries a risk of surgical site infection. 4 We believe that the staged approach as a concept of damage control surgery can be a safe and effective strategic option for complicated fractures, such as polytrauma and open fractures. 3 We agree that our protocol may increase some costs.…”
Section: Dear Editormentioning
confidence: 99%
“…However, the surgical operation causes great damage to soft tissue. Therefore, there has been much controversy about postoperative complications, such as wound infection and nonhealing[ 2 ]. With the in-depth development of minimally invasive treatment of calcaneal fractures, many doctors use the tarsal sinus approach to fix calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%